1993
DOI: 10.1111/j.1570-7458.1993.tb01736.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay for evaluating attraction of the phorid fly, Megaselia halterata to compost colonized by the commercial mushroom, Agaricus bisporus and to 1‐octen‐3‐ol and 3‐octanone

Abstract: A bioassay chamber was developed to evaluate the attraction of the phorid fly pest, Megaselia halterata (Wood) (Diptera, Phoridae), to volatiles from mushroom compost colonized by the commercial mushroom, Agaricus bisporus (Fungi, Agaricaceae) and to its volatile constituents, 1‐octen‐3‐ol and 3‐octanone. The bioassay chamber consisted of a large round container which was attached, via glass tubes, to three removable sample cups situated below the container. Once a fly had entered a sample cup, the flatly cut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 10 publications
1
31
0
1
Order By: Relevance
“…2), did not elicit behavioral activity except in females exposed to the highest dose. This result agrees with the report of Pfeil and Mumma (1993), who observed that high doses of 3-octanone seemed to produce deterrency in females of the phorid fly, Megaselia halterata. produced the same effect in males at two of the three tested doses.…”
Section: Discussionsupporting
confidence: 93%
“…2), did not elicit behavioral activity except in females exposed to the highest dose. This result agrees with the report of Pfeil and Mumma (1993), who observed that high doses of 3-octanone seemed to produce deterrency in females of the phorid fly, Megaselia halterata. produced the same effect in males at two of the three tested doses.…”
Section: Discussionsupporting
confidence: 93%
“…It is also used as a compost attractant for the phorid fly, Megaselia halterata 48 and as an avoidance cue for the parasitoid Lariophagus distinguendus 49.…”
Section: Discussionmentioning
confidence: 99%
“…Both preventive and curative treatments for mushroom flies would be improved if they were based on an in-depth knowledge of fly behaviour. In contrast, in an olfactometer study, mated and unmated female M. halterata showed no attraction to 1-octen-3-ol and 3-octanone, and were deterred by high concentrations of these compounds (Pfeil & Mumma, 1993). No studies have been done with sciarid flies.…”
Section: Introductionmentioning
confidence: 91%
“…There is also pressure on growers from retailers to reduce insecticide use in response to consumer concerns about pesticide residues. For phorid flies, Burrage (1981) and Pfeil & Mumma (1993) demonstrated that female M. halterata are attracted to a spawned composted substrate, but provided conflicting evidence on the attractiveness of mushroom volatile compounds. Both preventive and curative treatments for mushroom flies would be improved if they were based on an in-depth knowledge of fly behaviour.…”
Section: Introductionmentioning
confidence: 99%